The Role of Social Capital in The Social Networks of Flores Community Groups in Migrating to Denpasar Bali - Pandhu Nagara Prijatna (Program Studi Pendidikan IPS, 2025)
Bali, in addition to being a tourist destination, is also utilized as a migration destination for the public due to the availability of job opportunities in various fields. In the migration process, people from outside Bali often bring different cultures and backgrounds compared to the indigenous communities. Bali is often chosen as a migration destination by people from Flores, driven by economic and educational factors, as well as its geographical accessibility and rapid infrastructure development. In this migration process, these communities frequently use social capital as a tool to build social networks in order to achieve their migration goals. Social capital, which is binding, serves as the foundation for relationships built between individuals, forming groups that are homogeneous and exclusive. Based on Putnam's concept of social capital, this study will examine the role of social capital in the social networks of Flores communities migrating to Denpasar, Bali. This research uses a qualitative research method with an explanatory approach, allowing for an in-depth analysis of the phenomenon.